Media, Erotics, and Transnational Asia - Mankekar, Purnima; Schein, Louisa (Duke University Press, 2012)
Drawing on methods and approaches from anthropology, media studies, film theory, and cultural studies, the contributors to Media, Erotics, and Transnational Asia examine how mediated eroticism and sexuality circulating across Asia and Asian diasporas both reflect and shape the social practices of their producers and consumers. The essays in this volume cover a wide geographic and thematic range, and combine rigorous textual analysis with empirical research into the production, circulation, and consumption of various forms of media. Taken together, the essays offer fresh insights into research on gender, erotics, media, and Asia transnationally conceived.Contributors. Anne Allison, Tom Boellstorff, Nicole Constable, Heather Dell, Judith Farquhar, Sarah L. Friedman, Martin F. Manalansan IV, Purnima Mankekar, Louisa Schein, Everett Yuehong Zhang.